Study on the policy implementation of the Guangdong-Hong Kong-Macao joint graduate training program and regional talent development - Sirui Li; Johnny Fat Iam Lam (PLoS ONE, 2025)
To address the existing literature’s neglect of the micro-mechanisms involved in implementing joint postgraduate training policies in the Guangdong–Hong Kong–Macao Greater Bay Area, this study applies resource dependence theory to examine the logic of organisational interactions and their impact on talent development. Based on an analysis of 47 joint cultivation projects through qualitative case studies, the study identifies symbiotic, dominant, and competitive dependency relationships among cooperative entities, shaped by differences in resource endowments, which profoundly influence the stability of cooperation models. Policy effectiveness is primarily achieved through two intermediary mechanisms: “resource integration,” which consolidates financial, human, and knowledge resources, and “collaborative governance,” which builds an institutionalised and organised collaborative network. Significant differences exist between “university–university” and “university–institute” models in terms of both resource integration and governance effectiveness. Policy implementation enhances the quality and scale of talent cultivation while simultaneously promoting the development of the regional innovation ecosystem. The findings indicate that the effectiveness of joint cultivation hinges on micro-governance grounded in resource dependence at the implementation level. Future policy optimisation should prioritise balanced resource allocation and the institutionalisation and standardisation of cooperation models, thereby facilitating the transformation of regional talent governance from a “policy-driven” to a “system-driven” approach.